2009
DOI: 10.1007/s00381-009-1029-x
|View full text |Cite
|
Sign up to set email alerts
|

What has inflammation to do with traumatic brain injury?

Abstract: The initiation and orchestration of inflammation in TBI, as in other tissues, is complex and multifactorial encompassing pro- and anti-inflammatory cytokines, chemokines, adhesion molecules, complement factors, reactive oxygen and nitrogen species, and other undefined factors. It is evident that inflammation can have both beneficial and detrimental effects in TBI, but the mechanisms underlying this dichotomy are mostly unknown. Modification of the inflammatory response may be neuroprotective. Monitoring inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 40 publications
0
124
0
8
Order By: Relevance
“…TBI initiates a cascade of inflammatory processes including the release of proinflammatory mediators (43), which contributes to the acute pathologic processes and long-term neuronal damage following TBI (28). In this article, we found that brain levels of TNF-α and IL-6 increased significantly at 4 h after TBI and UH and ghrelin treatment dose dependently decreased brain levels of TNF-α and IL-6 under such conditions.…”
Section: Discussionmentioning
confidence: 66%
“…TBI initiates a cascade of inflammatory processes including the release of proinflammatory mediators (43), which contributes to the acute pathologic processes and long-term neuronal damage following TBI (28). In this article, we found that brain levels of TNF-α and IL-6 increased significantly at 4 h after TBI and UH and ghrelin treatment dose dependently decreased brain levels of TNF-α and IL-6 under such conditions.…”
Section: Discussionmentioning
confidence: 66%
“…Neuro-inflammation represents an important pathological process in secondary injury after TBI (68). Resident astrocytes and microglia are usually the initial cells that promote an inflammatory cascade following tissue injury, and bioactive proteins associated with the activation of these cells are often used as biomarkers of TBI (69,70).…”
Section: Microenvironmentmentioning
confidence: 99%
“…Excessive inflammation and release of proinflammatory cytokines could induce secondary brain injury which might lead to a serious outcome, including death [7]. Apoptosis could also be induced by inflammation in TBI via triggering apoptosis-related receptors on CNS cells and downstream apoptosis programs [6]. Apoptotic neural cell death has been found in TBI patients and in experimental TBI models [8] and inhibition of apoptosis was found to exert a beneficial effect in TBI [5].…”
Section: Introductionmentioning
confidence: 99%
“…In TBI, the brain cells are damaged by mechanical force, which results in the release of substances including intracellular components and blood components. These substances then activate the inflammatory cells, including microglia and astrocytes, that are resident in the central nervous system (CNS) and lead to proinflammatory cytokine release, including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and interferon-γ (IFN-γ) among others [6]. Excessive inflammation and release of proinflammatory cytokines could induce secondary brain injury which might lead to a serious outcome, including death [7].…”
Section: Introductionmentioning
confidence: 99%